New land governance models and management scenarios: Fitting Forest Management Units (FMUs) for forested landscapes outside forest zones in Indonesia - Daulay, Muhammad Haidar; Susanti, Fitria Dewi; Laraswati, Dwi; Arthalina, Erliza C.; Maryudi, Ahmad (Forest and Society, 2023)
Many parts of non-forest zones (Areal untuk Penggunaaan Lain/APL) in Indonesia are forested but are however under intense pressure from unsustainable practices and conversion. To help preserve forested APL zones, the Ministry of Environment of Forestry is envisioning the integration of forested APL areas into the operational activities of the Forest Management Units/ FMUs (Kesatuan Pengelolaan Hutan/KPH), a management arm of the forest administration. Under the current governance arrangements, FMUs are not tasked to manage the areas. In this paper, we developed new governance arrangements and management scenarios that permit management of forested APL by FMUs based on iterative processes and intensive consultation with related stakeholders. We developed three plausible broad scenarios: 1) the handing over forested APLs to FMUs, 2) co-management, and 3) FMUs to provide technical assistance for preserving forested APLs. We further detailed the three scenarios into five different models. Our scenarios of institutional arrangements and management models are by no means prescriptive and readily operationalized on the ground. Instead, the processes by which the scenarios and models were developed can be adopted when the FMUs intend to develop more detailed scenarios that reflect specific situations and conditions.